2020
DOI: 10.1038/s41467-020-18544-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic antenna coupling to hyperbolic phonon-polaritons for sensitive and fast mid-infrared photodetection with graphene

Abstract: Integrating and manipulating the nano-optoelectronic properties of Van der Waals heterostructures can enable unprecedented platforms for photodetection and sensing. The main challenge of infrared photodetectors is to funnel the light into a small nanoscale active area and efficiently convert it into an electrical signal. Here, we overcome all of those challenges in one device, by efficient coupling of a plasmonic antenna to hyperbolic phonon-polaritons in hexagonal-BN to highly concentrate mid-infrared light i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 50 publications
0
56
0
Order By: Relevance
“…Very recently, Castilla et al. [ 106 ] innovatively employed a novel method by combining plasmonic antenna and hyperbolic phonon‐polaritons in hexagonal‐BN to effectively improve the performance of graphene‐based mid‐IR photodetector. The photodetector exhibits excellent properties such as high responsivity (27 mA W −1 ), noise‐equivalent‐power (82 pW/Hz), and the response time reduced to 17 ns.…”
Section: Methods For Improving the Properties Of Photodetectorsmentioning
confidence: 99%
“…Very recently, Castilla et al. [ 106 ] innovatively employed a novel method by combining plasmonic antenna and hyperbolic phonon‐polaritons in hexagonal‐BN to effectively improve the performance of graphene‐based mid‐IR photodetector. The photodetector exhibits excellent properties such as high responsivity (27 mA W −1 ), noise‐equivalent‐power (82 pW/Hz), and the response time reduced to 17 ns.…”
Section: Methods For Improving the Properties Of Photodetectorsmentioning
confidence: 99%
“…19a) have been used to compensate for the mismatch between the large area of the incoming radiation and the small photoactive area of the detector. 55,264,[273][274][275][276][277] At GHz frequencies, microwave resonators (see Fig. 19b) have been used to couple light with 99% efficiency to graphene bolometers.…”
Section: Photodetectorsmentioning
confidence: 99%
“…Several of these sensitivity-enhancement strategies have been combined, in order to create high-performance long-wavelength photodetectors that operate at room-temperature. In the mid-IR region, where light absorption in graphene is particularly low due to Pauli blocking, Castilla et al 264 reported a PTE photodetectors based on clean a hBN-encapsulated graphene p–n junction with a responsivity of ∼27 mA W −1 (see Fig. 19c ), an NEP of ∼80 pW Hz −0.5 and a fast rise time 17 ns.…”
Section: Applicationsmentioning
confidence: 99%
“…Characterizing these properties with simultaneously high spatial and spectral resolution is difficult but essential for the rational design of advanced materials with novel functionalities [10][11][12][13][14]. Today, a number of studies have made progress in this direction through a variety of near-field imaging and spectroscopy techniques [15][16][17][18][19][20][21][22][23], yet considerable work still lies ahead to better understand material design principles and characterization methods in the IR spectral regime.…”
Section: Introductionmentioning
confidence: 99%